2007
DOI: 10.1248/bpb.30.2229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Curcuma longa and C. aromatica by LAMP

Abstract: We have developed a novel method for the identification of Curcuma longa and C. aromatica called "loop-mediated isothermal amplification (LAMP)," based on trnK gene sequences. LAMP employs four primers that recognize six regions on the target DNA. Cycling elongation was initiated when the four primers were annealed to the target DNA. Amplifications were detected by measuring turbidity due to the formation of magnesium pyrophosphate. We designed allele-specific primer sets for C. longa and C. aromatica, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 6 publications
(4 reference statements)
0
22
0
Order By: Relevance
“…In our previous work, amplification was detected from 55 to 70 min at DNA concentrations of 0.5 to 10.0 ng, which are the same as the concentrations used in this study. 4) Moreover, the set of primers for P. ginseng could be used to distinguish P. ginseng from P. japonicus despite the very slight differences in alignment. In genus Panax, P. japonicus is most closely related to P. ginseng genetically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, amplification was detected from 55 to 70 min at DNA concentrations of 0.5 to 10.0 ng, which are the same as the concentrations used in this study. 4) Moreover, the set of primers for P. ginseng could be used to distinguish P. ginseng from P. japonicus despite the very slight differences in alignment. In genus Panax, P. japonicus is most closely related to P. ginseng genetically.…”
Section: Resultsmentioning
confidence: 99%
“…Many convenient methods to detect single-nucleotide polymorphisms (SNPs) have been developed, including polymerase chain reaction (PCR)-restriction fragment-length polymorphism (RFLP) 1) and TaqMan assay. 2) In particular, loop-mediated isothermal amplification (LAMP) 3,4) is convenient because the reaction could be conducted under isothermal conditions, thereby facilitating amplification. LAMP employs four kinds of primers and amplification proceeds only when all the primers are annealed to the target DNA.…”
mentioning
confidence: 99%
“…[160][161][162] In another study, Sasaki and Nagumo reported rapid identification of C. longa and C. aromatica by LAMP method. [163] A study conducted by Sigrist et al showed genetic diversity of turmeric germplasm (C. longa; Zingiberaceae) using microsatellite markers to discover genetics and molecular research.…”
Section: Molecular Marker Analysis Inmentioning
confidence: 99%
“…19,20) It does not need any special devices or experienced technicians; thus, it is widely used for various purposes, such as detecting viruses and medicinal herbs. [21][22][23][24] One of the most species-specific genes in C. sativa is the THCA synthase gene that consists of a 1632 bp open reading frame. THCA synthase gene was cloned and polymorphism analysis revealed that 63 nucleotide substitutions divided the species into two chemotypes: the THCA-rich type (drug type), such as marijuana, and the THCA-poor type (fiber type), such as hemp.…”
Section: 7)mentioning
confidence: 99%